Preferences for interventions designed to increase cervical screening uptake in non‐attending young women: How findings from a discrete choice experiment compare with observed behaviours in a trial. (28th October 2019) - Campbell, Helen E.; Gray, Alastair M.; Watson, Judith; Jackson, Cath; Moseley, Carly; Cruickshank, Margaret E.; Kitchener, Henry C.; Rivero‐Arias, Oliver
Abstract: Background: Young women's attendance at cervical screening in the UK is continuing to fall, and the incidence of invasive cervical cancer is rising. Objectives: We assessed the preferences of non‐attending young women for alternative ways of delivering cervical screening. Design: Postal discrete choice experiment (DCE) conducted during the STRATEGIC study of interventions for increasing cervical screening uptake. Attributes included action required to arrange a test, location of the test, availability of a nurse navigator and cost to the National Health Service. Setting and participants: Non‐attending young women in two UK regions. Main outcome measures: Responses were analysed using a mixed multinomial logit model. A predictive analysis identified the most preferable strategy compared to current screening. Preferences from the DCE were compared with observed behaviours during the STRATEGIC trial. Results: The DCE response rate was 5.5% (222/4000), and 94% of respondents agreed screening is important. Preference heterogeneity existed around attributes with strong evidence for test location. Relative to current screening, unsolicited self‐sampling kits for home use appeared most preferable. The STRATEGIC trial showed this same intervention to be most effective although many women who received it and were screened, attended for conventional cytology instead. Conclusions: The DCE and trial identified the unsolicited self‐sampling kit as the most preferred/effective intervention. The DCE suggested that the decision of some women receiving the kit in the trial to attend for conventional cytology may be due to anxieties around home testing coupled with a knowledge that ignoring the kit could potentially have life‐changing consequences.